Goals and Objectives of the Court Sentence - Airapetean, Artur (Journal of Danubian Studies and Research, 2022)
In mutual connection, these provisions make it possible to most clearly understand both the essence of justice in criminal cases and to fully formulate the concept of an act adopted in its course - a court verdict, to reveal its inherent properties and requirements. This is the most important task of the theory of criminal procedure. The only basis for guilt or its absence, as well as the need to bring or exempt from criminal liability and punishment, is a court verdict, which contributes to the fight against crime, strengthening the rule of law and protecting human rights. It is this principle that gives us a real guarantee in strengthening the rule of law, in pursuing a unified criminal procedure policy, in protecting a person from illegal prosecution or non-criminal liability.